Vasil Levski: iz krivinite na literaturnata ikonografija : sbornikăt e posveten na 180-godišninata ot roždenieto na Vasil Levski - Lipčeva-Prandževa, Ljubka; Getova, Elena (Az-buki, Nacionalno izdatelstvo za obrazovanie i nauka, 2018)
Dedicated to the 180th anniversary of the birth of Vassil Levski, this collection gathers in one place the research efforts of literary writers and historians. The aim is tracing the way of the narrative about the historical personality to the sacred status of the national icon of the Apostle. The achieving of this scientific task intertwines the poetry of the "canonization strategist" (Hristo Botev), the words of today's lyricists, the memory of the associates, the "written by the hand of the Apostle", the results of an Olympiad in Taraklia (Moldova), the English press, the today’s children book and even the name of a mystical regiment The research efforts face the mystery of Apostle’s path into and out of monasticism, the words of veterans and philosophers, the ode and the rhapsody, the camera and the paint brush, the sound and the letter... To draw a never-ending journey, that will forever - and everywhere, accompany the Bulgarian spirit
Keywords: Bulgaria -- History -- 1762-1878